Surgical resection of pediatric PRETEXT III and IV hepatoblastoma: A retrospective study investigating the need for preoperative chemotherapy - Xiongwei Wu; Xiongwei Wu; Jianyong Wang; Yuhe Duan; Yusheng Liu; Yao Liu; Xin Chen; Nan Xia; Qian Dong; Qian Dong (Frontiers in Pediatrics, 2022)
ObjectiveThis study analyzed the feasibility of upfront surgical resection for pediatric PRETEXT III and IV hepatoblastoma (HB).Summary Background DataNeoadjuvant chemotherapy is recommended for patients with PRETEXT III and IV HB to obtain a chance of curative surgery. However, chemotherapy can cause toxic side effects and adverse outcomes, and the PRETEXT staging system may overstage the patients. Therefore, whether preoperative chemotherapy is necessary for HB patients remains unclear.MethodsThe clinical data of 37 children who underwent surgical resection for PRETEXT III and IV HB at our hospital were obtained retrospectively. Patients were divided into the neoadjuvant chemotherapy group (NCG; n = 19) and the routine surgery group (RSG; n = 18). Clinicopathologic characteristics, treatment regimens, and outcomes were compared between the groups.ResultsThe RSG had a lower incidence of portal vein involvement than the NCG (p < 0.002). The estimated 3-year event-free survival rates were similar (RSG: 89 ± 0.7% and NCG: 79 ± 0.9%, p = 0.3923). The RSG underwent fewer courses of chemotherapy than the NCG (five vs. six; p < 0.001). Furthermore, the RSG had lower incidences of febrile neutropenia, myelosuppression, and gastrointestinal reactions (all p < 0.05). The severity of surgery-related complications did not differ significantly.ConclusionUpfront surgical resection in children with PRETEXT III and IV HB is safe and feasible, and reduces the total number of courses and side effects of chemotherapy. The degree of vascular involvement is the most important consideration when evaluating resectability during diagnosis.